Neuropsychological Profile of Intellectually Gifted Children: A Systematic Review. (17th April 2022) - Bucaille, Aurélie; Jarry, Christophe; Allard, Justine; Brochard, Sylvain; Peudenier, Sylviane; Roy, Arnaud
Abstract: Objective: The term intellectually gifted (IG) refers to children of high intelligence, which is classically measured by the intelligence quotient (IQ). Some researchers assume that the cognitive profiles of these children are characterized by both strengths and weaknesses, compared with those of their typically developing (TD) peers of average IQ. The aim of the present systematic review was to verify this assumption, by compiling data from empirical studies of cognitive functions (language, motor skills, visuospatial processing, memory, attention and executive functions, social and emotional cognition) and academic performances. Method: The literature search yielded 658 articles, 15 of which met the selection criteria taken from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses model. We undertook a qualitative summary, to highlight any discrepancies between cognitive functions. Results: IG children exhibited better skills than TD children in a number of domains, including attention, language, mathematics, verbal working memory, shifting, and social problem solving. However, the two groups had comparable skills in visuospatial processing, memory, planning, inhibition, and visual working memory, or facial recognition. Conclusion: Although IG children may have some strengths, many studies have failed to find differences between this population and their TD peers on many other cognitive measures. Just like any other children, they can display learning disabilities, which can be responsible for academic underachievement. Further studies are needed to better understand this heterogeneity. The present review provides pointers for overcoming methodological problems and opens up new avenues for giftedness research.